Juggling Forms and Fabrics (ModaPalavra e-periódico, 2016)
This study aims to compare four methods which focuseson the manipulation of different shapes and fabrics. In order to generate alternative and more creative solutions to the current market and can be applied during the preparation of the product or the final piece. The operationalization of this study was performed in the discipline "shape manipulation" of the Drafiting MBA Class at the Feevale University in the year 2015. The methods worked were: Singer (2013), Rutzky and Palmer (2011) and Roberts (2013). In addition to these it was also carried out an exercise consisting of an amalgamation of techniques passed on by the teacher of the discipline. To this end, it sought to verify the differences between each method and the raw material used. The ultimate goal of discipline is the development of a piece that use at least three techniques taught. Each methodology has reached unexpected results focused on different niches such as commercial and conceptual.
Keywords: manipulation of form; concept form; comparison methodology